Implementation science in hybrid randomized controlled trials: a state-of-the-art systematic review. - Liu, Mark G; Comber, Elouise; Martin, Andrew; Roberts, Natasha; Trott, Mike; Costa, Nathalia; Foster, Nadine E; Hickman, Ingrid J (JBI Evidence Implementation, 2026)
Introduction: Hybrid randomized controlled trials (RCTs) combine effectiveness and implementation aims to accelerate evidence translation. As this is a new yet evolving methodology, it is timely to review the characteristics and reporting quality of hybrid RCTs, and how implementation science theories, models and frameworks (TMFs) have been used in this context. Methods: Citation-indexed databases (Web of Science, Scopus) were searched from 2012 (inception of "hybrid" terminology) to 2025 for RCTs that were identified as "hybrid" in the title/abstract/keywords and that cited and applied a TMF. RCT design and implementation characteristics were extracted and analyzed descriptively. Reporting quality assessment followed the Standards for Reporting Implementation Studies (StaRI). Results: Of the 1,846 initial hits, 111 papers were included, comprising 52 main results papers, 37 protocols, and 22 secondary papers. Most RCTs were published in the past 5 years (79%), conducted in North America (62%), in primary care/community settings (50%), and calculated sample sizes using the clinical effectiveness outcome (64%). TMFs were mostly used to inform implementation outcomes (88%) versus implementation strategies (52%). The most common TMFs were the Reach, Effectiveness, Adoption, Implementation, Maintenance Framework (RE-AIM) (44%) and Proctor's taxonomy of implementation outcomes (29%). Reporting quality was stronger for clinical intervention components, with fewer RCTs reporting the rationale and fidelity of implementation strategies (27%) compared to the clinical intervention (60%). Conclusions: Hybrid RCTs that apply TMFs are increasing, yet there is evidence that maturation is warranted. Clinical effectiveness rather than implementation remains the focus of most hybrid RCTs. More deliberate application and reporting of implementation science TMFs may improve the quality of future hybrid RCTs. http://links.lww.com/IJEBH/A518